2018
DOI: 10.1111/irv.12506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seasonal and pandemic influenza on health‐related quality of life, work and school absence in England: Results from the Flu Watch cohort study

Abstract: BackgroundEstimates of health‐related quality of life (HRQoL) and work/school absences for influenza are typically based on medically attended cases or those meeting influenza‐like‐illness (ILI) case definitions and thus biased towards severe disease. Although community influenza cases are more common, estimates of their effects on HRQoL and absences are limited.ObjectivesTo measure quality‐adjusted life days and years (QALDs and QALYs) lost and work/school absences among community cases of acute respiratory i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 21 publications
2
53
1
1
Order By: Relevance
“…Comparing our study to the Flu Watch prospective cohort study, we found that the QALY loss for an RSV episode is less than the QALY loss for a confirmed Influenza H1N1 episode, which is estimated to have mean 4·4 × 10 −3 (range -2·5–18·2 × 10 −3 ) across all ages. 22 However, our estimates are similar to the QALY loss for cases of respiratory disease in the same study which were not confirmed to be Influenza, but were confirmed to suffer from a fever and reported coughing/sore throat (mean 2·6 × 10 −3 (range -69·2–39·7 × 10 −3 ) across all ages). We cannot compare the QALY loss due to the confirmed RSV episodes in children under the age of five (3·823 × 10 −3 (95% CI 0·492–12·766 × 10 −3 )), with values from the Flu Watch because the confirmed RSV infections were recruited dependent on an infection being severe and requiring medical attention.…”
Section: Discussionsupporting
confidence: 79%
“…Comparing our study to the Flu Watch prospective cohort study, we found that the QALY loss for an RSV episode is less than the QALY loss for a confirmed Influenza H1N1 episode, which is estimated to have mean 4·4 × 10 −3 (range -2·5–18·2 × 10 −3 ) across all ages. 22 However, our estimates are similar to the QALY loss for cases of respiratory disease in the same study which were not confirmed to be Influenza, but were confirmed to suffer from a fever and reported coughing/sore throat (mean 2·6 × 10 −3 (range -69·2–39·7 × 10 −3 ) across all ages). We cannot compare the QALY loss due to the confirmed RSV episodes in children under the age of five (3·823 × 10 −3 (95% CI 0·492–12·766 × 10 −3 )), with values from the Flu Watch because the confirmed RSV infections were recruited dependent on an infection being severe and requiring medical attention.…”
Section: Discussionsupporting
confidence: 79%
“…Eighteen population‐specific articles have been included in this Special Edition—including five from Asia, four from Africa, four from Europe, three from North America, and one each from South America and the Middle East . (Figure and Table ) This reflects a broad geographical breadth of new research, and these data will add to our understanding of the burden of disease worldwide, especially in LMICs.…”
Section: New Series Of Burden Studiesmentioning
confidence: 99%
“…The most common outcomes were deaths attributable to influenza, used in nine studies, and severe acute respiratory infections (SARI) or its equivalent, used in eight studies . Another seven studies measured excess or absolute hospitalizations due to influenza, and five studies measured community or outpatient visits . Some studies were less representative for the entire country than others—there were 10 studies that collected data from across the country, although most national estimates were calculated with the help of extrapolations and appropriate adjustments for demographic differences …”
Section: New Series Of Burden Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The IPW-PS analysis, however, showed different results in the sensitivity analysis. Previous studies reported differently about difference of QOL score and duration of symptoms between influenza and ILI [32,33], so further work would be helpful in this specific area.…”
Section: Discussionmentioning
confidence: 93%